Adulterated Meat Processed Products Detection using Combination of FTIR and Chemometrics - Agustin Rafikasari; Any Guntarti; Anton Yudhana (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2026)
Indonesia has the world's largest Muslim population in 2025 and high demand for halal food products, including sausage. Differences in meat prices increase the risk of adulteration, which is wild boar or pork can adulterate beef or chicken. The adulteration can be detected using FTIR combined with chemometrics. The aim of this study was to investigate the adulteration in sausages by analyzed the fingerprint FTIR spectra combining with chemometrics. This study conducted by physicochemical analysis and scanning the extracted fat at the mid-infrared region using FTIR to collect spectral data. Qualitative and quantitative analyses were performed on the fingerprint region using chemometrics of Partial Least Square (PLS) and Principal Component Analysis (PCA), respectively to provide best modeling. The PLS calibration model for the relationship between actual values and predicted value of three binary mixed meats obtained from 1399 – 1321 cm-1, 1770 – 1681 cm-1, 780 – 650 cm-1. The calibration models demonstrated strong linearity, with R² values ranging from 0.9367 to 0.9884. The chicken–beef model exhibited the lowest RMSEC (5.85), indicating superior predictive accuracy. Although the chicken–pork model showed the highest R² (0.9884), its higher RMSEC (7.32) suggests reduced prediction precision. The chicken–wild boar model displayed the lowest R² and highest RMSEC, indicating greater model uncertainty, likely due to increased spectral similarity and matrix complexity. Fifteen marketed products analyzed. PCA of FTIR data demonstrated clear discrimination between halal-labeled and pork-containing sausages based on lipid profile differences, highlighting its potential as a rapid screening tool for halal authentication.